Residual stresses in Ti₄₁¸₅Zr₄₁¸₅Ni₁₇ quasi-crystalline ribbons measured by X-ray diffraction - Malykhin, S. (Functional Materials, 2007)
Using X-ray diffraction, strain measurement, scanning electron microscopy, and microprobe analysis, structure, composition and stress state were studied in Ti₄₁¸₅Zr₄₁¸₅Ni₁₇ quasi-crystalline ribbons prepared by one-side melt solidification on the rotating wheel. The macro-stresses have been found to be distributed inhomogeneously across the ribbon section. On the side contacted with cooler, compressive stress up to 130 MPa acts, while the stress sign changes at the opposite side. The total level of residual stresses is defined by the quenching rate from melt. The observed peculiarities of stress distribution along the normal to solidification front are explained by temperature field inhomogeneity across the ribbons as well as by release of the solidification heat.